5(c-2)=5(4+c)+3

Simple and best practice solution for 5(c-2)=5(4+c)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(c-2)=5(4+c)+3 equation:


Simplifying
5(c + -2) = 5(4 + c) + 3

Reorder the terms:
5(-2 + c) = 5(4 + c) + 3
(-2 * 5 + c * 5) = 5(4 + c) + 3
(-10 + 5c) = 5(4 + c) + 3
-10 + 5c = (4 * 5 + c * 5) + 3
-10 + 5c = (20 + 5c) + 3

Reorder the terms:
-10 + 5c = 20 + 3 + 5c

Combine like terms: 20 + 3 = 23
-10 + 5c = 23 + 5c

Add '-5c' to each side of the equation.
-10 + 5c + -5c = 23 + 5c + -5c

Combine like terms: 5c + -5c = 0
-10 + 0 = 23 + 5c + -5c
-10 = 23 + 5c + -5c

Combine like terms: 5c + -5c = 0
-10 = 23 + 0
-10 = 23

Solving
-10 = 23

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -2x+7a=10 | | -37-8y+18=-25y+9+13y | | 7n+19=5n+5 | | 3x/4=1/4x | | 7(-6x+5)=497 | | -4(p+1)=2(8-4p) | | 9/15=2x-1/3x | | 0=-5y-5+4x | | h(x)=6x^2+5 | | 4x+8x+x=260 | | 3x-14=3x+11 | | -x^2=-28 | | -40+12x=-57+8x | | 13w-19w=-12 | | X+2Y-30+3X-Y+X+Y=180 | | 2g(X)+3=6 | | 0.12(x+2000)=5760 | | 13-44=4(x-2)-3 | | 12x+4=-2x+88 | | X(2x+1)=2 | | 1(x+y)= | | -5(x+1)-10=13+2 | | -5+7x+5(x-10)+15=2(x+6)-2(2x+4)+10x-61 | | -3x-3(2-3x)=8+6x | | X^4-x^2=8 | | 2x+17=8x+17 | | (x^3-3x^2-25x+75)= | | ax^2+ax+4=0 | | In(x-3)=3 | | 3b+30= | | 3x+2+24+32=180 | | 3x+8-7+13x=75 |

Equations solver categories